2014
DOI: 10.1016/j.ajhg.2014.11.001
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Functional Noncoding Variant at the GWAS-Implicated MIR137/MIR2682 Locus Might Confer Risk to Schizophrenia and Bipolar Disorder

Abstract: Schizophrenia (SZ) genome-wide association studies (GWASs) have identified common risk variants in >100 susceptibility loci; however, the contribution of rare variants at these loci remains largely unexplored. One of the strongly associated loci spans MIR137 (miR137) and MIR2682 (miR2682), two microRNA genes important for neuronal function. We sequenced ∼6.9 kb MIR137/MIR2682 and upstream regulatory sequences in 2,610 SZ cases and 2,611 controls of European ancestry. We identified 133 rare variants with minor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
73
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 76 publications
7
73
1
Order By: Relevance
“…Abnormalities in dendrite arborization have been reported in several neuropsychiatric disorders. Surprisingly, our findings of increased dendrite arborization did not parallel previous postmortem findings in schizophrenia (41); despite this, the increased dendrite arborization associated with 16p11.2 duplication during development may lead to premature maturation of synapses, as has been shown when schizophrenia-associated MIR137 expression is reduced (42,43). However, 16p11.2 duplications are also associated with ASD and seizure disorder, and the cellular phenotypes we identified may be more reflective of these disorders (16,44,45), such as the hypothesized increased brain connectivity in ASD.…”
Section: Discussioncontrasting
confidence: 54%
“…Abnormalities in dendrite arborization have been reported in several neuropsychiatric disorders. Surprisingly, our findings of increased dendrite arborization did not parallel previous postmortem findings in schizophrenia (41); despite this, the increased dendrite arborization associated with 16p11.2 duplication during development may lead to premature maturation of synapses, as has been shown when schizophrenia-associated MIR137 expression is reduced (42,43). However, 16p11.2 duplications are also associated with ASD and seizure disorder, and the cellular phenotypes we identified may be more reflective of these disorders (16,44,45), such as the hypothesized increased brain connectivity in ASD.…”
Section: Discussioncontrasting
confidence: 54%
“…Cis -acting miRNA QTLs ( cis -mirQTLs) are generally located in the transcription regulatory regions of the miRNA locus 58,59 . For example, an SNV that is associated with a risk of schizophrenia in the enhancer of mir-137 weakens binding of the transcription factor YY1, leading to decreased miR-137 expression 60 . The relatively high prevalence of cis -mirQTLs is illustrated by one study in which RNA-seq of small RNAs of more than 450 genetically diverse human LCLs from the 1000 Genomes Project revealed that 60 of the 644 expressed mi RNAs that were detected (approximately 9%) contained cis -mirQTLs 4 .…”
Section: Variants Affect Mirna-mediated Regulationmentioning
confidence: 99%
“…Additionally, different SNPs (rs1625579; rs1198588, rs1702294) in the upstream region of the host gene for miR-137 have been strongly associated with SCZ (Cummings et al, 2013; Green et al, 2013; Psychosis Endophenotypes International et al, 2014; Ripke et al, 2013; Schizophrenia Psychiatric Genome-Wide Association Study, 2011; Whalley et al, 2012). Besides SNPs, variable number tandem repeats (VNTRs) and rare variants have been also reported within the same MIR137 locus (Duan et al, 2014; Strazisar et al, 2015; Warburton et al, 2015). Recently, Warnica et al reported CNVs at eight loci (1q21.1, 2q13, 12q21.31, 14q32.33, 15q11-15q13, 16p11.2, 16p13.11, and 19q13.42), which overlap with a total of 25 miRNAs (Warnica et al, 2015), providing abundant evidence for the potential contribution of disrupted miRNA levels to the underlying pathophysiology.…”
Section: Genetic Variants In Mirna-related Genesmentioning
confidence: 99%